Community, Time, and (Con)text: A Dynamical Systems Analysis of Online Communication and Community Health among Open‐Source Software Communities. Issue 5 (17th May 2022) - Paxton, Alexandra; Varoquaux, Nelle; Holdgraf, Chris; Geiger, R. Stuart
Abstract: Free and open‐source software projects have become essential digital infrastructure over the past decade. These projects are largely created and maintained by unpaid volunteers, presenting a potential vulnerability if the projects cannot recruit and retain new volunteers. At the same time, their development on open collaborative development platforms provides a nearly complete record of the community's interactions; this affords the opportunity to study naturally occurring language dynamics at scale and in a context with massive real‐world impact. The present work takes a dynamical systems view of language to understand the ways in which communicative context and community membership shape the emergence and impact of language use—specifically, sentiment and expressions of gratitude. We then present evidence that these language dynamics shape newcomers' likelihood of returning, although the specific impacts of different community responses are crucially modulated by the context of the newcomer's first contact with the community.